Research progress of phase change cold energy storage materials used in cold chain logistics of aquatic products. (April 2023) - Feng, Tianping; Ji, Jun; Zhang, Xuelai
Abstract: Phase change cold energy storage materials with approximately constant phase transition temperature and high phase change latent heat have been initially used in the field of cold chain logistics. However, there are few studies on cold chain logistics of aquatic products, and no relevant reviews have been found. Therefore, the research progress of phase change cold energy storage materials used in precooling, processing, packaging, transportation and storage of aquatic products was reviewed. In addition, the cold chain logistics process of aquatic products, commonly used low-temperature preservation technology and the influence of temperature fluctuation on the quality of aquatic products were introduced. Some phase change cold energy storage materials in cold chain temperature zone of aquatic products developed by researchers in recent years and existing inorganic eutectic water-salt solution phase change cold energy storage materials in sub-zero temperature were collected. It has reference value for future development of phase change energy storage materials for cold chain logistics of aquatic products. And the common encapsulation forms of phase change materials were introduced. The problems of the cold chain from fishing to selling of aquatic products and the solutions of applying phase change cold energy storage materials were summarized. Finally, some prospects for the application of phase change cold energy storage materials in cold chain logistics of aquatic products in the future were put forward. Highlights: The research progress of phase change cold storage materials used in cold chain logistics of aquatic products was reviewed in detail for the first time. Phase change cold storage materials for cold chain of aquatic products developed in recent years were collected. The research progress of phase change cold storage materials is introduced in terms of precooling, processing and packaging, transportation and storage of aquatic products. The existing problems and solutions in various stages of aquatic products cold chain logistics were summarized.